The elephant and the dragon in contemporary life sciences : a call for decolonising global governance - Zhang, Joy Yueyue, 1981-; Burton, Saheli Datta (Inscriptions (Manchester University Press), 2022)
This book demonstrates that the 'subversiveness' assumed in China's and India's rise in the life sciences reflects many of the regulatory challenges that are shared globally. It stresses a decolonial imperative for science governance to be responsive and effective in a cosmopolitan world.